Optical and Reflective Characteristics Measurement and Focal Length Calculation of a Hollow Tetrahedral Corner and a Solid Highly Retroreflective Cubes - Mohammad Saeed Marouf (International Journal of Optics)
Corner cubes are one of the most important optical tools used in new optical devices and optical LIDAR. This paper compares two different designs of the hollow and solid tetrahedral corner cubes and determines the relation between the Retroreflection index and the surface quality N and the surface flatness ∆N and its effect on the focal length of the hollow and solid corner cube.